2023
DOI: 10.1002/smll.202207278
|View full text |Cite
|
Sign up to set email alerts
|

A Highly Translatable Dual‐arm Local Delivery Strategy To Achieve Widespread Therapeutic Coverage in Healthy and Tumor‐bearing Brain Tissues

Abstract: Drug delivery nanoparticles (NPs) based entirely on materials generally recognized as safe that provide widespread parenchymal distribution following intracranial administration via convection‐enhanced delivery (CED) are introduced. Poly(lactic‐co‐glycolic acid) (PLGA) NPs are coated with various poloxamers, including F68, F98, or F127, via physical adsorption to render particle surfaces non‐adhesive, thereby resisting interactions with brain extracellular matrix. F127‐coated PLGA (F127/PLGA) NPs provide marke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…21−24 Drug loading processes encompass physical and chemical approaches, where physical encapsulation offers simplicity and cost-effectiveness but may suffer from offtargeted molecular degradation. 25,26 Conversely, chemical conjugation with polymer materials provides advantages such as hydrophobic drug solubility, controlled pharmacokinetics, and reduced drug release in large quantities. 27,28 A previous study evaluated tetrazine-functionalized boron-rich carbon dots, which demonstrated rapid clearance and low tumor absorption following intravenous administration in a mouse HER2-positive tumor model.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…21−24 Drug loading processes encompass physical and chemical approaches, where physical encapsulation offers simplicity and cost-effectiveness but may suffer from offtargeted molecular degradation. 25,26 Conversely, chemical conjugation with polymer materials provides advantages such as hydrophobic drug solubility, controlled pharmacokinetics, and reduced drug release in large quantities. 27,28 A previous study evaluated tetrazine-functionalized boron-rich carbon dots, which demonstrated rapid clearance and low tumor absorption following intravenous administration in a mouse HER2-positive tumor model.…”
Section: ■ Introductionmentioning
confidence: 99%
“…In the face of the ongoing investigation into toxicity, the integration of nanoparticles into drug delivery systems remains achievable through active or passive targeting mechanisms. Drug loading processes encompass physical and chemical approaches, where physical encapsulation offers simplicity and cost-effectiveness but may suffer from off-targeted molecular degradation. , Conversely, chemical conjugation with polymer materials provides advantages such as hydrophobic drug solubility, controlled pharmacokinetics, and reduced drug release in large quantities. , A previous study evaluated tetrazine-functionalized boron-rich carbon dots, which demonstrated rapid clearance and low tumor absorption following intravenous administration in a mouse HER2-positive tumor model . Naproxen, a widely recognized nonsteroidal anti-inflammatory drug (NSAID), has recently garnered attention for its potential anticancer properties, as evidenced by its efficacy as a COX-2 inhibitor in clinical trials. Our previous study proved that a combination of naproxen with nanoparticles results in better activity regarding the treatment of several diseases. Despite these promising properties, there is limited research on the kinetic release model that typically occurs when B-CDs are combined with anticancer medications, both in vitro and in vivo.…”
Section: Introductionmentioning
confidence: 99%